The Effect of Playing Exercises (Analytical – Holistic) On Tactical Performance of Young Soccer Players Aged 14 – 16 years old - Abed, Ismael; Hamdullah, Ahmed (Journal of Physical Education, 2018)
The Effect of Playing Exercises (Analytical – Holistic) On Tactical Performance of Young Soccer Players Aged 14 – 16 years oldThe research aimed at classifying the subject into four groups; two controlling groups and two experimental groups as follows, each of the two controlling groups consisted of (8) players used the traditional method. The two experimental groups also consisted of (8) for analytical cognitive style and (8) for holistic cognitive style designed by the researcher. The researcher used the experimental method. The subjects were (32) players from Al Shula sport club. The training program lasted for 12 weeks with three training sessions per week. The data was collected and treated using SPSS. The researcher concluded using playing exercises have a positive effect on improving tactical performance in the experimental group. Finally the researcher recommended the necessity of using playing exercises as well as making similar studies on other age groups in soccer (young, youth, advance, and women’s soccer).